Defect-enriched red phosphorus nanosheets as efficient and stable photothermal absorber material for interfacial solar desalination - Shridharan, Tatachari Santhanagopalan; Sivanantham, Arumugam; Tan, Runfa; Hong, Seo Yeong; Kim, Dong Hoe; Cho, In Sun (Desalination, 2023)
The development of efficient photothermal materials has gained increasing attention for solar thermal-energy conversion. A good photothermal material has a strong light-absorption property, low thermal conductivity, high wettability, and high solar-to-thermal conversion efficiency. In this study, we prepared uniform, sub-micron, and defect-rich red phosphorus (RP) nanosheets via a simple ball-milling method to demonstrate their efficient and durable solar steam generation properties. Three RPs of different sizes were prepared by controlling the milling time (0 h: RP0, 30 h: RP30, and 60 h: RP60). Notably, RP60 exhibited the smallest particle (lateral) size, nanosheet morphology, and defect-rich surface. Furthermore, RP60 exhibited the distinctive properties of a small band gap (1.44 eV), low thermal conductivity (0.07 W/m·K), and low heat capacity (0.66 J/g·K) with exceptional wettability. With simulated sunlight illumination (100 mW/cm2, 1 sun), the RP60 photothermal absorber demonstrated a high water evaporation rate of 1.34 kg/m2·h with a stable solar steam generation efficiency of 74.1 % for over 10 h. A one-dimensional water path and porous polyurethane support facilitated the water supply, large contact area, heat localization, and steam escape. By employing plasmonic resonance-heating silver nanoparticles on the RP60, we achieved a significantly improved solar steam generation efficiency of over 96.0 % and a water evaporation rate of 1.75 kg/m2·h. This study highlights the critical role of morphology, particle size, and defects control in improving the photothermal properties for efficient and durable interfacial seawater desalination.
Keywords: Interfacial solar steam generation; Low thermal conductivity; Photo-thermal; Plasmonic resonance heating; Plasmonic resonances; Property; Red phosphorus; Solar steam; Steam generation; Water evaporation; Interfacial solar steam generation; Nanosheets; Plasmonic resonance heating; Red phosphorus; Surface defects